Patients with Opioid Use Disorder Have Increased Readmission Rates, Emergency Room Visits, and Costs Following Hallux Valgus Procedures. Issue 4 (22nd October 2020) - Parrish, James M.; Vakharia, Rushabh M.; Benson, Dillon; Hoyt, Aaron K.; Jenkins, Nathaniel W.; Kaplan, Jonathan R.; Rush, Augustus J.; Roche, Martin W.; Aiyer, Amiethab A.
Category: Ankle; Bunion; Midfoot/Forefoot; Other Introduction/Purpose: Patients with a history of opioid use disorder (OUD) have been shown to incur more severe medical complications, higher readmission rates, and increased cost following various orthopedic procedures. There is a scarcity in the literature investigating the effects of OUD following a hallux valgus procedure. Therefore, the purpose of this study was to evaluate whether OUD patients undergoing a hallux valgus correction are at greater odds of: 1) readmission rates, 2) emergency room (ER) visits, and 3) costs. Methods: Patients undergoing a hallux valgus correction with a history of OUD were identified using a health insurance claims database. To search for patients undergoing hallux valgus surgical corrections the following current procedural terminology (CPT) medical codes were used: 28290, 28292, 28293, 28294, 28296, 28297, 28298, 28299, 28306, and 28307. To include all eligible patients the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM) codes were also utilized, including: 77.51 and 77.59. OUD patients were matched to non-opioid use disorder (NUD) patients in a 1:4 ratio by age, sex, Elixhauser-Comorbidity Index (ECI), diabetes mellitus, hyperlipidemia, hypertension, and tobacco use. Primary outcomes analyzed included odds of 90-day readmission rates, 30-day emergency room visit, and 90-day episode of care costs. Pearson's chi-squared test was used to compare demographics. Logistic regression analysis calculated odds-ratios for readmission and ER visits. Welch's t-test was used for significance in ECI and cost between cohorts. Results: The query yielded 6, 318 patients (OUD=1, 276; NUD=5, 042) who underwent a hallux valgus correction. There were no significant difference between any of the compared age ranges (p=0.859, p=0.952, p=0.909, p=0.961), ECI (p=1.000) and comorbidities between OUD and NUD patients. OUD patients had higher incidence and odds of 90-day readmission rates (9.56 vs. 6.04%; OR: 1.55, p<0.001) and 30-day ER visits (.86 vs. .35%; OR: 2.42, p=0.021) compared to controls. OUD patients also incurred significantly greater 90-day episode of care costs ($7, 208.28 vs. $6, 134.75, p<0.0001) compared to NUD patients. Conclusion: Patients with a history of OUD who underwent a hallux valgus correction had a higher odds ratio of 90-day readmission rates, 30-day emergency room visits, and 90-day total global episode of care cost compared to those with NUD. These findings expand on a rapidly growing body of current literature that demonstrate OUD increases numerous costs associated with outcomes of foot and ankle surgery. OUD is a risk factor for poor post operative outcomes for patients undergoing a hallux valgus correction. The findings of this study are likely to improve preoperative counseling and selection when addressing patients with preoperative opioid use.